The Role of Kiai In Establishing The Accountability of The Nahdlatul Ulama - Novi Wulandari; Ali Djamhuri; Ari Kamayanti (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
The purpose of this research is to analyze and describe in depth the reality of the role of Kiai in establishing the Nahdlatul Ulama (NU) accountability. The research perspective used in this study is to use the interpretive paradigm with qualitative research methods and use a collective case studies approach (collective or multiple case study). The use of collective case studies is carried out because in this study not only carried out at the PBNU central office (Pengurus Besar Nahdlatul Ulama), but also at the regional administrator's office, branch administrator’s office, muslimat administrator’s office, and Islamic boarding school. From the results of the research it was found that besides the role of Kiai, NU also had its own way of accountability. NU's accountability process is called Typical Accountability of Lillahita'ala and Ikhlas in the style of Nahdlatul Ulama.